البيتون عالي المقاومة بالمواد المحلية, تحضيره, ودراسة خواصه وسلوكه. - أحمد عبود; نزيه منصور; الشريفة بهيجة آل الفضل (Tishreen University, 2016)
برزت أهمية البيتون عالي المقاومة في الآونة الأخيرة لدخوله في تصنيع أغلب عناصر وأجزاء المنشآت البيتونية, وكذلك في تنفيذ المنشآت المدنية الخاصة, كقواعد الجسور والأبراج العالية و الأعمدة والمنصات التي تحمل المنشآت النفطية, في البحار والمحيطات. يهدف البحث إلى تصيمم خلطات بيتونية ذات مقاومات أسطوانية(55-65-75)MPa وفق الكود الأمريكي ACI-211-4R-93 ,وذلك باستخدام إحضارات محلية وإضافات مناسبة, مع شرح لطريقة التصميم المستخدمة. ومن ثم دراسة تغيير مخطط )الإجهاد - التشوه ) تجريباً على الضغط البسيط للعينات السابقة, وذلك من خلال الأجهزة المتوفرة ,وتمت مقارنتها مع المخططات التي تم الحصول عليها حسابياً. تم تقييم قانون السلوك لمخطط (الإجهاد - التشوه) ومعامل المرونة المأخوذ من المخطط . استنتجت مجموعة من النتائج والتوصيات الخاصة بالموضوع والتي تمكن من تطبيق نتائج البحث على أرض الواقع. Recently, the importance of high Strength concrete has appeared due to its application in manufacturing most of the concrete structures and members, as well as to its importance in the implementation of civilian facilities like bridge bases, skyscrapers and in implementing the columns and platforms which carry oil installations carried out in the oceans and seas. The research aims to design concrete mixtures with cylindrical resistors ( 55- 65- 75 Mpa) according to the American code AcI-211-4R-93 by using local and appropriate additions as well as explaining the method used in designing. Then, studying the transformation in stress strain curve - deformation (σ- ζ ) undergoing a simple pressure on the previous samples throughout the available devices. Then, it was compared to the charts obtained mathematically .Law behaviour of stress strain and deformation curve was rated, in addition to modulus of elasticity taken from the chart. Couple of results and recommendations related to the issue were concluded, those which were applied in praxis .